Creativity and art therapies to promote healthy aging: A scoping review - Galassi, Flavia; Merizzi, Alessandra; D’Amen, Barbara; Santini, Sara (Frontiers in Psychology, 2022)
The present review aims to investigate the value of the creative approach proper to Art Therapies (ATs) in the population of healthy older adults. Adopting the American Art Therapy Association (AATA) definition of Art Therapy (AT) and Cohen's conceptual framework for the psychological conceptualization of the relationship between arts and health in later life, the article aims to shed light on current knowledge about the effectiveness of ATs for the prevention of common age-related conditions. The intent is to sensitively capture subthreshold situations of distress, which are often not taken into account and which mainly concern psychological aspects crucial in the multidimensional perspective of healthy aging. After an initial electronic search on 3 databases, 12 articles were selected and examined. Thematic analysis of the results identified four major themes: improving cognitive performance and proprioception; enhancing self-identity and meaningful life; reducing feelings of loneliness and depressive symptoms; and the importance of socialization. These are all aspects that form the basis of prevention of psychological distress and enhancement of mental well-being, in connection to the paradigm of healthy aging.